PENGARUH LITERASI KEUANGAN SYARIAH DAN PENERAPAN ETIKA BISNIS ISLAM TERHADAP KINERJA UMKM BATIK KHAS JAMBI - Divva Anggara Putra; Ambok Pangiuk; Habriyanto; Eri Nofriza; Beid Fitrianova (ICONS: Islamic Economics Journal, 2026)
The performance of MSMEs can be seen from the level of Islamic financial literacy possessed by business actors. A good understanding of Islamic finance helps manage businesses more professionally and sustainably. In addition, the performance of MSMEs can also be influenced by the application of Islamic business ethics. The main principles in Islamic business ethics include compliance with Islamic law which prohibits the practice of riba (interest), gharar (uncertainty), and maisir (gambling). The purpose of this study is to analyze the influence of Islamic Financial Literacy and the implementation of Islamic business ethics on the performance of Jambi Typical Batik MSMEs. The research method used is quantitative, with a sample of 30 respondents. The research analysis used is multiple linear regression. The results of the study showed that Islamic Financial Literacy has an influence on the performance of Jambi Typical Batik MSMEs with a significance value of 0.043 <0.05. The application of business ethics has an influence on the performance of Jambi Typical Batik MSMEs with a significance value of 0.002 <0.05. Sharia Financial Literacy and the Implementation of Business Ethics jointly influence the performance of Jambi's Typical Batik MSMEs. The coefficient of determination indicates that Sharia Financial Literacy and the Implementation of Business Ethics can influence the performance of Jambi's Typical Batik MSMEs by 79.4%.